2012
DOI: 10.5923/j.chemistry.20120204.02
|View full text |Cite
|
Sign up to set email alerts
|

Cationic Surfactants from Arginine: Synthesis and Physicochemical Properties

Abstract: The present invention concerns the preparation of cationic surfactants derived from the condensation of an acid chloride, preferably a fatty acid with a number of carbon atoms 8, 9 and 14 with esterified amino acids, preferably basic-type amino acids, like (L)-arginine. The method comprises a first step in which the esterification of the amino acid with an alcohol is performed and a second step for the condensation with a chloride of fatty acid, using Schotten Baumann conditions. These surfactants constitute a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 20 publications
2
10
0
1
Order By: Relevance
“…C 11 DMM and dodecanoate can form electrostatically bound heterodimers with very high surface activity [ 26 ]. The CMC value of LAE was at the concentration 1.0–1.1 mmol/dm 3 , in agreement with the value reported in [ 18 ], lower than in other reports (see Table 1 ). The surface tension value at CMC (σ CMC ) was 25 mN/m, much lower than for typical cationic surfactants, closer to σ CMC for nonionic surfactants and characteristic for di-chain or Gemini surfactants [ 27 , 28 ].…”
Section: Resultssupporting
confidence: 92%
“…C 11 DMM and dodecanoate can form electrostatically bound heterodimers with very high surface activity [ 26 ]. The CMC value of LAE was at the concentration 1.0–1.1 mmol/dm 3 , in agreement with the value reported in [ 18 ], lower than in other reports (see Table 1 ). The surface tension value at CMC (σ CMC ) was 25 mN/m, much lower than for typical cationic surfactants, closer to σ CMC for nonionic surfactants and characteristic for di-chain or Gemini surfactants [ 27 , 28 ].…”
Section: Resultssupporting
confidence: 92%
“…This reflects the well-known influence of hydrogen bonding capacity and HLB to enhance the formation of supramolecular structures 21. Additionally, lipopeptides bearing longer aliphatic chains display lower CAC than their shorter counterparts, a trend extensively reported for similar lipopeptides 22.…”
supporting
confidence: 65%
“…LAE alone is a potent antimicrobial agent, and its incorporation of chitosan has led to the creation of the most effective coating on microbial proliferation even at low doses. The antimicrobial activity of LAE has been associated with a positive charge in its structure (Singare & Mhatre, 2012), but its antimicrobial mechanism has not been fully characterized. Some researchers have suggested that bacterial membranes are the main target of LAE (Becerril et al., 2013; Coronel‐León et al, 2016; Pattanayaiying et al., 2014; Rodriguez et al., 2004).…”
Section: Resultsmentioning
confidence: 99%